Piaget and Freud: about childhood memory - Arboccó de los Heros, Manuel (2009)
In the following work, it is meditated starting from the search of some parallelism between Jean Piaget’s studies and Sigmund Freud’s work, around the topic of one of the most important mental processes: the memory; and more specifically the infantile memory.